Pathogenic memory plasma cells in autoimmunity - Chang, Hyun-Dong (Curr Opin Immunol, 2019)
• Memory plasma cells are long-lived but require specialized niches for their survival. • Memory plasma cells are refractory to conventional immunosuppression. • Pathogenic memory plasma cells represent ‘roadblocks’ to response to conventional therapy. • Strategies for (selective) targeting of memory plasma cells are in preclinical and clinical tests.